Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Rumah Makan Jaso Bundo di Batuphat Timur Kota Lhokseumawe - Khaira Zikrani Malrizwa; Rahmaniar Rahmaniar; Naufal Bachri; T. Edyansyah (Jurnal Intelek Insan Cendikia, 2025)
This study aims to analyze the influence of price, product quality, and service quality on purchasing decisions at Rumah Makan Jaso Bundo in Batuphat Timur, Lhokseumawe City. This study uses a quantitative method with purposive sampling technique and multiple linear regression analysis. The results show that price, product quality, and service quality have a positive and significant influence on purchasing decisions. The more suitable the price is with the value perceived by consumers, the higher the product quality, and the better the service quality, the higher the likelihood of consumers making a purchase. This study contributes to the development of marketing strategies and improving consumer purchasing decisions at Rumah Makan Jaso Bundo.